The Influence of Work Discipline on Employee Performance in Manufacturing - Destiana Kumala; Denok Sunarsi; Rofiq Noorman Haryadi; Dedi Sukardi (Doctoral Program of Social Science Pasundan University, 2023)
This research is an associative quantitative research, with a significance level of ? = 0.05 (5%) and a confidence level of 95%. The sample used random sampling with a sample of 123. The data collection method used a primary data system, namely observation and questionnaires and secondary data, namely literature study. Instrument testing uses validity tests and reliability tests, and data analysis methods use frequency distribution analysis, simple linear regression, correlation coefficient, coefficient of determination, and t test. Data calculations were carried out manually and using SPSS. The research results show that the discipline variable in the frequency distribution analysis is perceived as good at 3.41 and employee performance is good at 3.44. In the linear regression analysis Y = 30.408 + 0.679 So Ho is rejected and Ha is accepted. Thus, these results explain that there is a significant influence between discipline on employee performance at the Indovickers Furnitama manufacturer.